if(x-1) is a factor of p(x), then a)p(0)=1 b)p(1)=0 c)p(-1)=0 d)p(0)=-1

Rivka Thorpe 2021-03-18 Answered
if(x-1) is a factor of p(x), then
a)p(0)=1
b)p(1)=0
c)p(-1)=0
d)p(0)=-1
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

liingliing8
Answered 2021-03-19 Author has 95 answers
Step 1
By factorization theorem, it is known that if for x=a, P(a)=0 for some polynomial P(x), then, (x-a) is a factor of P(x).
Since, (x-1) is a factor of P(x), then,
P(1)=0
Step 2
Hence, correct option is b
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more